2021
DOI: 10.1021/jacs.1c08159
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Amination of Polylactic Acid to Alanine

Abstract: In comparison to the traditional petroleum-based plastics, polylactic acid, the most popular biodegradable plastic, can be decomposed into carbon dioxide and water in the environment. However, the natural degradation of polylactic acid requires a substantial period of time and, more importantly, it is a carbon-emitting process. Therefore, it is highly desirable to develop a novel transformation process that can upcycle the plastic trash into value-added products, especially with high chemical selectivity. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 30 publications
(41 reference statements)
0
89
0
1
Order By: Relevance
“…The products include polymers with new properties, 898 liquid fuels, 899 waxes, 900 and platform molecules. 901 The C-H bonds in PE (HDPE, LDPE, LLDPE) can be oxidized to ketone or hydroxyl groups, which generates functionalized polymers with unique physical properties (e.g., strong adhesion, ability to be painted with common paint etc.). 898 The high-valent ruthenium-oxo species (polyfluorinated ruthenium porphyrin) catalyzes this process in the presence of 2,6dichloropyridine N-oxide and shows high reactivity without the incorporation chlorine or overoxidation to form esters at 120 °C.…”
Section: Functionalization Of Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The products include polymers with new properties, 898 liquid fuels, 899 waxes, 900 and platform molecules. 901 The C-H bonds in PE (HDPE, LDPE, LLDPE) can be oxidized to ketone or hydroxyl groups, which generates functionalized polymers with unique physical properties (e.g., strong adhesion, ability to be painted with common paint etc.). 898 The high-valent ruthenium-oxo species (polyfluorinated ruthenium porphyrin) catalyzes this process in the presence of 2,6dichloropyridine N-oxide and shows high reactivity without the incorporation chlorine or overoxidation to form esters at 120 °C.…”
Section: Functionalization Of Polymersmentioning
confidence: 99%
“…Tian et al reported that Ru/TiO2 can catalyze the amination of ether groups in PLA in ammonia solution at 140 °C. 901 Alanine can be produced by this process with high selectivity in the absence of hydrogen. In most of the cases, other chemicals (e.g., light alkanes, water, halogens) need to be cofed for the functionalization of the waste plastics.…”
Section: Functionalization Of Polymersmentioning
confidence: 99%
“…Traditional hydrogenation catalysts based on Pt group metals (e.g., Pt, Pd, and Ru) [12][13][14][15][16][17][18][19][20] offer the benefits of comparatively mild operation conditions, high selectivity, high efficiency, and excellent stability but are costly, which has inspired the development of cheaper yet efficient alternatives. The selection of a suitable support was found to be important for improving catalytic performance at reduced noble metal loadings.…”
mentioning
confidence: 99%
“…The addition of Ru not only provides an active metal site for dehydrogenation, but also greatly promotes the NH 3 adsorption for amination reaction. 39 The role of metallic oxide in amination has also been discussed in many research studies. Zhang et al designed a Ru/ZrO 2 catalyst in the aldehyde/ketone amination, where RuO 2 acted as a Lewis acid and activated the carbonyl group.…”
Section: Resultsmentioning
confidence: 99%